Is universal screening for hepatitis C infection prior to commencing antitumour necrosis factor‐α therapy necessary?. (December 2013) - Reid, C.T.; De, C.; Hall, W.; Collins, P.; Lally, A.; Kirby, B.
Summary Background Screening for hepatitis C virus (HCV) prior to the commencement of antitumour necrosis factor (anti‐TNF)‐α therapies for dermatological disease is recommended for all patients. Objectives To determine the incidence of HCV infection among dermatology patients who were screened for HCV infection prior to commencing anti‐TNF‐α therapies. Methods We reviewed the HCV infection status of all patients attending our dermatology department who had been tested for evidence of HCV infection between January 2005 and November 2012. We identified patients who had been tested as part of routine screening prior to commencing anti‐TNF‐α therapy using dermatology departmental records. Results In total, 215 patients were screened for HCV infection prior to commencing anti‐TNF‐α therapies. Among this group, 143 patients (66·5%) were male and 72 (33·5%) were female. None of these patients tested positive for active HCV infection. One patient tested positive for HCV antibody with negative HCV antigen and HCV RNA. This indicated previous HCV infection that had cleared. This patient had abnormal liver function tests and a history of alcohol excess. Conclusions There were no cases of active HCV infection diagnosed through pretreatment anti‐TNF‐α screening in our department, which is located in a low‐prevalence area for HCV infection. In view of the lack of evidence of harm associated with anti‐TNF‐α use in HCV‐infected patients, we propose that screening for HCV infection in low‐prevalence areas should be targeted to those with pre‐existing risk factors. This is consistent with current guidelines from the Royal College of General Practitioners. Targeted screening rather than universal screening may be a safe and cost‐effective option among patients being evaluated for anti‐TNF‐α therapies.